2019
DOI: 10.17977/um002v11i12019p056
|View full text |Cite
|
Sign up to set email alerts
|

The Role Mediation of Export And Foreign Debt in Influences Exchanges Rate on Foreign Exchange Reserves: Evidence from Indonesian

Abstract: The purpose of this study is to examine and analyze the role of export and foreign debt mediation in the effect of exchange rate on foreign exchange reserves. And test and analyze the effect of exchange rate on exports, foreign debt and foreign exchange reserves and the effect of exports and foreign debt on foreign exchange reserves in Indonesia in 1999-2015. The type of research data is secondary data sourced from Bank Indonesian and Central Bureau of Statistics. Data analysis with path analysis using AMOS 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Because the majority of foreign debt is used to cover the current account deficit and pay debt instalments, foreign debt indirectly promotes foreign exchange reserves (Premawari et al, 2019). The findings of this study are consistent with the findings of Indriany (2021) and Rahim et al (2019). Foreign loan funds are increasingly being used, encouraging an increase in foreign exchange reserves.…”
Section: Vecm Model Regressionsupporting
confidence: 90%
“…Because the majority of foreign debt is used to cover the current account deficit and pay debt instalments, foreign debt indirectly promotes foreign exchange reserves (Premawari et al, 2019). The findings of this study are consistent with the findings of Indriany (2021) and Rahim et al (2019). Foreign loan funds are increasingly being used, encouraging an increase in foreign exchange reserves.…”
Section: Vecm Model Regressionsupporting
confidence: 90%
“…The foreign debt positively and insignificantly influenced the change in the development of Indonesia's foreign exchange reserves during the period 1988-2017 because, in theory, foreign debt that is utilized productively can support the increase in foreign exchange reserves but in reality, Indonesia's foreign debt has not been invested productively so it does not produce a high rate of return in several years of research (Putri et al, 2017). It also means that if foreign debt increases but does not significantly affect the change in the number of Indonesian foreign exchange reserve that by previous research stating that foreign debt influences foreign exchange reserves (Rahim et al, 2019). Net exports positively and significantly affect the change in the development of Indonesian foreign exchange reserves (Ardianti & Swara, 2018).…”
Section: Figure 2 Gdp and Consumption In Indonesia (Us$)mentioning
confidence: 86%
“…The results showed that foreign debt had a positive and significant effect on foreign exchange reserves in Indonesia in 1996-2015 (Putri et al, 2017). Increasingly, funds from foreign loans are used, thus encouraging an increase in foreign exchange reserves (Rahim et al, 2019). Foreign debt and foreign exchange reserves have a positive relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The more types of goods that have such privileges produced by a country the more exports can be done (Sukirno, 2011). When exports increase, the country's income in the form of foreign currency (Rahim et al, 2019) or foreign exchange reserves will increase so that it is proven that it can increase foreign exchange reserves (Putri et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%